J. Hillis Miller's "Humanistic Discourse and the Others": Roundtable Discussion - Adams, Hazard; Behler, Ernst; Birus, Hendrik; Derrida, Jacques; Iser, Wolfgang; Krieger, Murray; Miller, Hillis; Pfeiffer, Ludwig; Readings, Bill; Wang, Ching-hsien; Yu, Pauline (Surfaces, 1996)
This roundtable discussion of "Humanistic Discourse and the Others", J. Hillis Miller's contribution to the first International Conference for Humanistic Discourses, was held in April, 1994. The papers of this first meeting of the ICHD have been published in volume 4 of Surfaces (1994).